Epidemiological characteristics of human adenovirus infections in China, 2020–2023 - Chongyang Li; Yitong Lin; Naiying Mao; Yixuan Gao; Ying Liu; Liwei Sun; Hui Zhang; Jin Xu; Maozhong Li; Feng Zhang; Xiaoqing Liu; Linqing Zhao; et al. (Biosafety and Health)
To better understand the epidemiological characteristics of human adenovirus (HAdV) infections in China during and after the coronavirus disease 2019 (COVID-19) pandemic, respiratory specimens were collected from 17,562 enrolled patients with acute respiratory infections (ARIs) in 14 sentinel surveillance provinces during 2020–2023. Eight common respiratory viruses were detected using commercially available nucleic acid detection kits. HAdV-positive cases were statistically analyzed for detection rates, geographic distribution, seasonal patterns, demographic characteristics, and co-infection status. The results of this study showed that the overall HAdV detection rate was 5.09 % (894/17,562) during 2020–2023, with a gradual decrease in the annual detection rate from 6.66 % in 2020 to 3.89 % in 2022 and a rebound in 2023 (5.19 %). The overall HAdV detection rate was significantly higher in the southern region (6.15 %) than in the northern region (4.76 %) (P < 0.001). The median age of patients with HAdV infection was 3 years, with infants aged 0–2 years accounting for the majority (41.39 %). HAdV-positive cases were detected throughout the year, with no clear seasonal pattern, and the HAdV epidemic in China during 2020–2023 may have been driven primarily by the virus infection in the southern region. Co-infections were frequent in HAdV-positive cases (overall rate: 36.01 %), primarily consisting of dual infections (79.28 %), with human rhinovirus and human respiratory syncytial virus being the most common coinfecting pathogens. In conclusion, this study suggested the significant regional and temporal variation in HAdV detection rate in China during 2020–2023, and thus ongoing surveillance should be conducted to elucidate the epidemiological dynamics of HAdV infections.